Evaluasi Keterampilan Komunikasi Interpersonal Antara Konselor Dengan Siswa, Staf Sekolah, dan Orangtua SMKN di Kota Malang - Galang Surya Gumilang (JKI (Jurnal Konseling Indonesia), 2016)
The purpose of this study are to know: (1) Evaluation of interpersonal communication skills between counselors and students, (2) Evaluation of interpersonal communication skills between counselor and school staff, (3) Evaluation of interpersonal communication skills between counselor and parents. Used study evaluation using a mixed method design, which combined quantitative and qualitative methods. Mixed Methods is a research method that use more than one method or with a combination of quantitative and qualitative approaches. Research instrument consists of a questionnaire of interpersonal communication skills and interpersonal communication skills interview guide. Results of research resulted in the description and analysis (1) Evaluation of interpersonal communication skills between counselors and students, (2) Evaluation of interpersonal communication skills between counselor and school staff, (3) Evaluation of interpersonal communication skills between counselor and parents.